2005
DOI: 10.1111/j.1471-4159.2005.03440.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased processing of APLP2 and APP with concomitant formation of APP intracellular domains in BDNF and retinoic acid‐differentiated human neuroblastoma cells

Abstract: The amyloid precursor protein (APP) belongs to a conserved gene family, also including the amyloid precursor-like proteins, APLP1 and APLP2. We have previously shown that all members of the APP protein family are up-regulated upon retinoic acid (RA)-induced neuronal differentiation of SH-SY5Y neuroblastoma cells. Here, we demonstrate that RA also affects the processing of APLP2 and APP, as shown by increased shedding of both sAPLP2 and sAPPa, as well as elevated levels of the APP intracellular domains (AICDs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 50 publications
1
48
0
Order By: Relevance
“…Western Blot Assay-Conditioned medium was collected and concentrated as described previously (21). Cells were harvested and analyzed by Western blot assay as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…Western Blot Assay-Conditioned medium was collected and concentrated as described previously (21). Cells were harvested and analyzed by Western blot assay as described previously (21).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that BDNF/TrkB signaling can affect APP expression levels, glycosylation and cleavage [16][17][18][19]. We have found that TrkB isoforms can differentially affect the processing and the expression levels of over-ex-pressed APP in SH-SY5Y neuroblastoma cells [20].…”
Section: Introductionmentioning
confidence: 82%
“…PMA was able to increase the ADAM activity signal in both cell lines (Figure 3 (a)). SH-SY5Y cells have been shown to display accumulation of sAPP- when treated with retinoic acid [16]. The ADAM10 promoter contains retinoic acid responsive elements (RARE), so we hypothesized that this increase sAPP- release is mediated by an increased transcription and maybe activity of ADAM10 in this cell line.…”
Section: Adam10 Activity Is Not Affected Bymentioning
confidence: 99%
See 2 more Smart Citations